2021
DOI: 10.1590/1679-78256514
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Jet Formation and Penetration Characteristics of Square cross-section Shaped Charge

Abstract: The jet morphology of square and circular cross-section shaped charge with same inscribed circle diameter were observed by conducting an X-ray experiment. Depth-of-penetration tests at standoffs 80 and 160 mm were also carried out. The jet formation was studied by using AUTODYN software. The results showed that the jet of square cross-section shaped charge consists of a condensed part and a non-condensed part. The condensed part has similar characteristics to the corresponding part of circular cross-section sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Their conclusions showed that the detonation radius over the longitudinal axis—restricted by the charge radius over the same axis—as well as the detonation wave in the charge and the force acting on the liner, were affected, eventually influencing the jet velocity and shape. Wang Y et al [ 10 ] obtained the morphology of the SCJ from shaped charges with square and circular cross-sections based on X-ray experiments. The results showed that the SCJ from the square cross-section shaped charge presented partially discrete phenomenon; they thought it could adjust the compaction rate of the SCJ from the square cross-section shaped charge through changing the inscribed circle diameter of the charge cross-section.…”
Section: Introductionmentioning
confidence: 99%
“…Their conclusions showed that the detonation radius over the longitudinal axis—restricted by the charge radius over the same axis—as well as the detonation wave in the charge and the force acting on the liner, were affected, eventually influencing the jet velocity and shape. Wang Y et al [ 10 ] obtained the morphology of the SCJ from shaped charges with square and circular cross-sections based on X-ray experiments. The results showed that the SCJ from the square cross-section shaped charge presented partially discrete phenomenon; they thought it could adjust the compaction rate of the SCJ from the square cross-section shaped charge through changing the inscribed circle diameter of the charge cross-section.…”
Section: Introductionmentioning
confidence: 99%